2001
DOI: 10.1080/00221320109597879
|View full text |Cite
|
Sign up to set email alerts
|

Values and Antisocial Behavior Among Spanish Adolescents

Abstract: A number of studies have indicated that delinquent adolescents have characteristic value systems. However, most of these studies have adopted a "known-groups" design--that is, they have compared institutionalized delinquents and non-institutionalized adolescents, assuming those adolescents to be non-delinquent. Designs of this type do not distinguish effectively between the statistical effects of delinquency and of institutionalization. In this study, the authors investigated relationships between values and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
2
9
0
4
Order By: Relevance
“…In men sample, there was no direct effect of boldness on any value, but the interactions suggested that boldness amplifies the negative effect of disinhibition for lower acquisition of conventional and self-realization values. Bearing in mind that the acquisition of conventional values is socially adaptive, and the acquisition of hedonism is related to socially risky and maladaptive behaviours, such as aggressive conflict management and delinquency (Romero et al, 2001;Franc et al, 2002), the association of boldness both with conventional and hedonistic values in women is in line with previous studies showing that boldness is both associated with indices of adaptive function, but also with psychological maladjustment, including aggression (Fanti, Kyranides, Drislane, Colins, & Andershed, 2016), lack of altruism and erratic lifestyle (Drislane & Patrick, 2016). Thus, our results suggest that in women boldness has both an adaptive AND VALUE ORIENTATIONS IN MEN AND WOMEN and maladaptive function.…”
Section: Discussionmentioning
confidence: 99%
“…In men sample, there was no direct effect of boldness on any value, but the interactions suggested that boldness amplifies the negative effect of disinhibition for lower acquisition of conventional and self-realization values. Bearing in mind that the acquisition of conventional values is socially adaptive, and the acquisition of hedonism is related to socially risky and maladaptive behaviours, such as aggressive conflict management and delinquency (Romero et al, 2001;Franc et al, 2002), the association of boldness both with conventional and hedonistic values in women is in line with previous studies showing that boldness is both associated with indices of adaptive function, but also with psychological maladjustment, including aggression (Fanti, Kyranides, Drislane, Colins, & Andershed, 2016), lack of altruism and erratic lifestyle (Drislane & Patrick, 2016). Thus, our results suggest that in women boldness has both an adaptive AND VALUE ORIENTATIONS IN MEN AND WOMEN and maladaptive function.…”
Section: Discussionmentioning
confidence: 99%
“…Sobre este aspecto, termos como delinqüência juvenil (Tate, Reppucci, & Mulvey, 1995), comportamento delinqüente (Davalos, Chavez, & Guardiola, 2005), comportamento anti-social (Romero, Sobral, Luengo, & Marzoa, 2001) e comportamento disruptivo (American Psychiatric Association, 1994;Loeber, Burke, Lahey, Winters, & Zera, 2000) são utilizados algumas vezes como sinônimos e, em outras, com significados completamente distintos (ver comentários de Pimentel, 2004).…”
Section: Comportamentos Anti-sociais E Delitivosunclassified
“…Porém, mesmo com inúmeras variáveis individuais e psicossociais capazes de promover programas de intervenções, ainda é destacável o papel dos valores humanos. O fato é que estudos que abordam o construto dos valores humanos vêm observando que uma adesão a valores mais pessoais ou individualistas é capaz de promover o uso de drogas, a amizade com jovens com condutas delinqüentes e as dificuldades na aprendizagem, enquanto que a adesão a valores sociais ou coletivistas inibiria tais fatores de risco (COELHO JÚNIOR, 2001;ROMERO et al, 2001;TAMAYO et al, 1995).…”
Section: Introductionunclassified